(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Assessing the nutritional status of elderly people being treated at Nghe An General Friendship Hospital. Subjects: Research on 290 patients over 60 years old receiving inpatient treatment at Nghe An General Friendship Hospital from January to June 2023. Methods: Cross-sectional descriptive study. Results: Men 49.7%, women 50.3%. Average age: 72.4±7.9. Age group 60-69: 42.4%, age group ≥ 80: 19%. Classification of nutritional status according to BMI: malnourished 13.4%, normal: 80.7% and overweight, obese: 5.9%; According to MNA: with nutritional risk: 75.8% and without nutritional risk: 24.2%; According to NRS: with nutritional risk: 54.1% and without nutritional risk: 45.9%. Conclusions: The malnutrition status in elderly people being treated at Nghe An General Friendship Hospital is still high and nutritional status classification according to BMI, MNA, NRS methods has differences in malnutrition rates.